2014
DOI: 10.3390/ijerph110504619
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and Antimicrobial Susceptibility of Staphylococcus epidermidis Strains from a Hospital Environment

Abstract: The hospital environment microflora comprise a wide variety of microorganisms which are more or less pathogenic and where staphylococci are one of the most common types. The aim of the presented study was to evaluate the prevalence of the biofilm forming coagulase-negative staphylococci (CoNS) in a hospital environment as a risk factor for nosocomial infections. Among 122 isolated and tested strains of CoNS the most frequent were: S. epidermidis—32 strains, S. haemolyticus—31 strains, S. capitis subsp. capiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…These survey findings and the literature 14,16 emphasize the need for evidence‐based practice guidelines that clearly delineate effective spot and hospital or facility standard cleaning practices to prevent bacterial growth and SSIs 14‐19 . Survey findings and the literature also showed that HCWs wear aprons and thyroid shields in hospitals or facilities where standard cleaning policies or procedures are lacking 14…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These survey findings and the literature 14,16 emphasize the need for evidence‐based practice guidelines that clearly delineate effective spot and hospital or facility standard cleaning practices to prevent bacterial growth and SSIs 14‐19 . Survey findings and the literature also showed that HCWs wear aprons and thyroid shields in hospitals or facilities where standard cleaning policies or procedures are lacking 14…”
Section: Discussionmentioning
confidence: 83%
“…Coagulase‐negative Staphylococcus is a major health care–associated pathogen that colonizes the skin 17 . The presence of normal skin flora that produces biofilm is an increased risk factor for SSIs 18 . In orthopedic surgeries involving implantation of prosthetic joints, such biofilms lead to the “microbial seeding” of implanted prosthetics 19 …”
Section: Manufacturers’ Information and Recommendationsmentioning
confidence: 99%
“…30,31 Coagulase-negative staphylococci (CoNS) such as S. epidermidis can cause serious hospital acquired infections and is a biofilm producing species. 32 Most common victims of S. epidermidis infection are premature newborns, patients with leukaemia, intravenous drug abuse, other malignancies and patients with indwelling polymer bodies, such as prosthetic devices or intravenous catheters. 33,34 The extracellular Polysaccharide Adhesins (PSA) is a significant virulence determinant and is required for biofilm formation and adhesion, which is encoded by the ica operon, and is subjected to phase variable regulation, and an on and off switching mechanism.…”
Section: Staphylococci and Ica Genesmentioning
confidence: 99%
“…35 Polysaccharide intercellular adhesin (PIA) is the main component involved in intercellular adhesion by staphylococci. 32,36 Stevens et al studied various protein components including PIA of biofilm in S. epidermidis and have suggested that PIA has a primary role in biofilm positivity while protein components contribute significantly towards the maturation of the biofilm. 37,38 PIA synthesis requires the presence of the ica operon because the enzymes which are involved in its synthesis are controlled by the intercellular adhesion operon (ica ADBC).…”
Section: Staphylococci and Ica Genesmentioning
confidence: 99%
“…The Congo red agar method does not quantitatively detect strong biofilms, which is measured by crystal violet staining (Croes et al, ). Additionally, slime‐positive strains on Congo‐red agar are not correlated with antibiotic sensitivity and biofilms (Wojtyczka et al, ).…”
Section: Introductionmentioning
confidence: 99%